Flood secure: building house resilience with intelligent flood management - Rosli, Muhammad Afiq Hakimi; Sulhan, Muhammad Aiman; Md Sin, Nor Diyana (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The design and construction of an Internet of Things (IoT)- integrated flood monitoring and alert systems using Arduino-based sensors are described in this technical study. Furthermore, of Ultrasonic, Water, and Float sensors, the system has a Blynk application that allows for real-time alert alerts. The system becomes an Internet of Things (IoT) device with real-time monitoring and automated reaction capabilities when wireless communication technology is included. To further reduce damage, the system has featured that automatically close house gates. The system monitors and controls flood conditions by processing data from various sensors using the Arduino microcontroller. Automated gate actuators are examples of responsive components that improve system functionality. Intelligent decision-making is built into the Arduino code, which also constantly controls the sensors and send alarms in response to predetermined water levels. With real-time IoT connectivity to enhance disaster preparation and safety, this IoT-Integrated Flood Monitoring and Response System gives an adaptable and scalable automated flood control solution.